Crack path and fracture surface modifications in cement composites (Fracture and Structural Integrity, 2015)
There is a tremendous increase in the use of high strength and high performance self-consolidating cementitious composites due to their superior workability and mechanical strengths. Cement composites are quasi-brittle in nature and possess extremely low tensile strength as compared to their compressive strength. Due to the low tensile strength capacity, cracks develop in cementitious composites due to the drying shrinkage, plastic settlements and/or stress concentrations (due to external restrains and/or applied stresses) etc. These cracks developed at the nanoscale may grow rapidly due to the applied stresses and join together to form micro and macro cracks. The growth of cracks from nanoscale to micro and macro scale is very rapid and may lead to sudden failure of the cement composites. The present paper reports the modifications in the crack growth pattern of the high performance cement composites to achieve enhanced ductility and toughness. The objective was accomplished by the incorporation of the micro sized inert particulates in the cement composite matrix. The results indicate that the incorporation of micro sized inert particles acted as the obstacles in the growth of the cracks thus improving the ductility and the energy absorption capacity of the self-consolidating cementitious composites.
Keywords: Fracture energy